2010
DOI: 10.1152/japplphysiol.00615.2009
|View full text |Cite
|
Sign up to set email alerts
|

Signals consistent with microbubbles detected in legs of normal human subjects after exercise

Abstract: Exercise may produce micronuclei (presumably gas-filled bubbles) in tissue, which could serve as nucleation sites for bubbles during subsequent decompression stress. These micronuclei have never been directly detected in humans. Dual-frequency ultrasound (DFU) is a resonance-based, ultrasound technique capable of detecting and sizing small stationary bubbles. We surveyed for bubbles in the legs of six normal human subjects (ages 28-52 yr) after exercise using DFU. Eleven marked sites on the left thigh and calf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Gas nuclei grow to become visible, and stable gas bubbles depend on the dissolved CO 2 gas concentration (Wilbur et al 2010; Lin et al 2000). Partial venous pressure of CO 2 ( P vCO 2 ) elevates during CPR and its causes are as follows (Suwa 1992; Halmagyi et al 1970; Suwa et al 1969; Chazan et al 1968; Weil et al 1986; Gudipati et al 1990; Lindner et al 1991): 1) increased arterial-venous difference of P CO 2 due to low cardiac output, 2) increased CO 2 production due to anaerobic metabolism progression, and 3) decreased CO 2 transport by the blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gas nuclei grow to become visible, and stable gas bubbles depend on the dissolved CO 2 gas concentration (Wilbur et al 2010; Lin et al 2000). Partial venous pressure of CO 2 ( P vCO 2 ) elevates during CPR and its causes are as follows (Suwa 1992; Halmagyi et al 1970; Suwa et al 1969; Chazan et al 1968; Weil et al 1986; Gudipati et al 1990; Lindner et al 1991): 1) increased arterial-venous difference of P CO 2 due to low cardiac output, 2) increased CO 2 production due to anaerobic metabolism progression, and 3) decreased CO 2 transport by the blood.…”
Section: Discussionmentioning
confidence: 99%
“…Second, PMCT findings could not morphologically differentiate whether the myocardial intravascular gas of the LV was in the artery or in the vein. However, tribonucleation and supersaturation of CO 2 , which are the two predominant theories of gas nuclei and bubbles origin (Wilbur et al 2010; Lin et al 2000), suggest that the gases were in the vein. Additionally, the presence of intravascular gas in the venula of pericardial fat may be indirect evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The question remains as to why cycling exercise did not produce benefi cial results. In a recent study carried out by Wilbur et al ( 31 ), a dual frequency ultrasound technique was used to detect microbubbles in the legs of subjects before and after cycling exercise. This technique would be useful to compare the amount of bubbles produced by different types of exercise and, in this case, Wilbur's results suggested that cycling did produce an increased amount of detectable microbubbles.…”
Section: Discussionmentioning
confidence: 99%
“…It has been known for at least half a century that, as noticed by Hayward in 1967 (11), "extremely gentle rubbing" of two solid objects inside a liquid under tension, which is otherwise stable against most forms of mechanical action (e.g., knocking on the container wall or stirring), readily induces nucleation. This tribonucleation is often cited as a plausible source of the microbubbles found in the limbs of humans and animals after physical exercise (12,13). Campbell (14) and Ikels (15) attributed the nucleation observed in these conditions to the pressure drop induced by the viscous flow in the space between two separating solid surfaces.…”
mentioning
confidence: 98%